Analisis efektivitas pemberian makanan tambahan terhadap indeks bb/u balita underweight - Desiana, Zahra Ratnawati; Rakhma, Luluk Ria; Kisnawaty , Sudrajah Warajati (Holistik Jurnal Kesehatan, 2025)
Background: Nutritional issues related to underweight remain a public health issue that impacts child growth and development. Supplemental feeding is one intervention taken to address underweight, particularly in early childhood, who are in a critical growth phase. The prevalence of underweight children in Indonesia reached 17.1%, while in Central Java the figure was 17.6% in 2022. In Sukoharjo Regency, the prevalence of underweight was recorded at 11.8%, with 228 cases reported in the Mojolaban Community Health Center area. This situation indicates the need for intervention to address the nutritional challenges faced by children. Purpose:  To analyze the effectiveness of supplementary feeding on the weight/age index of underweight toddlers. Method: A quasi-experimental study involving 100 underweight toddlers aged 12–60 months. Sampling was carried out through random sampling at the integrated service post within the Mojolaban Community Health Center area. Weight measurements were carried out using a digital scale specifically for children with an accuracy of 0.1 kg. The data obtained were analyzed using a weight-for-age (BW/A) z-score based on WHO guidelines. Normality testing was performed using the Shapiro-Wilk method, while differences were assessed using the Wilcoxon Signed Ranks Test with a significance level of p < 0.05. Results: There was an increase in BW/A in early childhood after a month-long (30-day) supplementary feeding intervention program. Children with normal nutritional status experienced an increase from 9.6% to 19.2%, while those in the severely malnourished category decreased from 14.4% to 10.6%. The nutritional status of underweight toddlers also decreased from 76% to 70.2%. Statistical analysis using the Wilcoxon Signed Ranks Test showed a p-value of 0.000 (p < 0.05), indicating a significant difference between BW/A values ​​before and after the supplementary feeding program. Conclusion: Supplemental feeding has an impact on the nutritional status of underweight toddlers, although the impact is not optimal and has not reached all targets equally. This supplemental nutrition intervention has the potential to increase its effectiveness through improvements in timing, quality, and family involvement in its implementation. Suggestion: Future research is recommended to extend the supplemental feeding period to observe the medium-term effects on the nutritional status of toddlers. Furthermore, a more in-depth review is needed, incorporating other variables, such as health background, eating habits, and environmental conditions that may influence nutritional status.   Keywords: Supplemental; Toddlers; Underweight; Weight/Age Index.   Pendahuluan: Masalah gizi terkait underweight masih tetap menjadi isu kesehatan masyarakat yang memengaruhi pertumbuhan dan perkembangan anak. Pemberian Makanan Tambahan (PMT) adalah salah satu langkah intervensi yang diambil untuk menangani masalah underweight, khususnya pada anak usia dini yang berada dalam fase pertumbuhan penting. Angka prevalensi anak underweight di Indonesia mencapai 17.1%, sementara di Jawa Tengah angkanya sebesar 17.6% pada tahun 2022. Di Kabupaten Sukoharjo, prevalensi underweight tercatat sebesar 11.8%, dengan 228 kasus yang dilaporkan di area Puskesmas Mojolaban. Situasi ini menandakan perlunya intervensi untuk menyelesaikan masalah gizi yang dihadapi oleh anak-anak. Tujuan: Untuk menganalisis efektivitas pemberian makanan tambahan terhadap indeks bb/u balita underweight. Metode: Penelitian kuasi eksperimen yang melibatkan 100 balita underweight berusia 12–60 bulan. Pengambilan sampel melalui random sampling di posyandu wilayah kerja Puskesmas Mojolaban. pengukuran berat badan menggunakan timbangan digital khusus anak dengan tingkat akurasi 0.1 kg. Data yang diperoleh dianalisis dengan z-score berat badan menurut umur (BB/U) berdasarkan pedoman dari WHO. Pengujian normalitas dilakukan menggunakan metode Shapiro-Wilk, sedangkan perbedaan data diuji menggunakan uji Wilcoxon Signed Ranks Test dengan tingkat signifikansi p < 0.05. Hasil: Adanya peningkatan berat badan berdasarkan usia (BB/U) pada anak-anak usia dini setelah program intervensi PMT selama sebulan (30 hari). Anak-anak dengan status gizi normal mengalami kenaikan dari 9.6% menjadi 19.2%, sedangkan kategori gizi sangat kurang mengalami penurunan dari 14.4% menjadi 10.6%. Status gizi balita gizi kurang juga turun dari 76% menjadi 70.2%. Analisis statistik menggunakan uji Wilcoxon Signed Ranks Test menunjukkan nilai p = 0.000 (p < 0.05), sehingga adanya perbedaan signifikan antara nilai BB/U sebelum dan sesudah program PMT dilaksanakan. Simpulan: Pemberian makanan tambahan (PMT) memengaruhi perubahan status gizi balita underweight, meskipun dampaknya belum optimal dan belum menjangkau semua sasaran secara merata. Intervensi gizi tambahan ini memiliki potensi untuk meningkatkan efektivitasnya melalui perbaikan dalam waktu, kualitas, dan keterlibatan keluarga dalam pelaksanaanya. Saran: Penelitian selanjutnya dianjurkan untuk memperpanjang periode PMT, sehingga dapat mengamati efek dalam jangka menengah pada status gizi anak balita. Selain itu, diperlukan tinjauan yang lebih mendalam dengan memasukkan variabel lain, seperti latar belakang kesehatan, kebiasaan makan, dan kondisi lingkungan yang bisa berpengaruh pada status gizi.   Kata Kunci: Balita; Indeks BB/U; Pemberian Makanan Tambahan (PMT); Underweight.